Assessment of Indonesian Higher Education Students’ Critical Thinking Based on Merrill’s First Principles of Instruction - Endang Mastuti Rahayu; W. Bandjarjani (Jurnal Pendidikan Indonesia, 2021)
Studies in Indonesian Higher Education students’critical thinking skills, have shown that they still need reinforcement. Hereby, Merrill’s First Principles of Instruction offers steps of activities to facilitate this. This article reports the results of a case study on the assessment of Indonesian Higher Education students’critical thinking skills in each step of Merrill’s First Principles of Instruction (Problem, Actication, Demonstration, Application, and Integration) during Classroom Action Research Course for students of batch 2017 of English Language Education Department. Through descriptive qualitative analysis of assessment rubric of critical thinking, it was found that the assessments given in each step of Merrill’s First Principles of Instruction could trigger the students’ critical thinking skills assisting them to manage to formulate proposal for conducting Classroom Action Research. This provides insights to craft assessment in line with Merrill’s First Principles of Instruction as to promote students’ critical thinking skills. Therefore, it could be suggested for other researchers to conduct similar research using more careful and detailed criteria of critical thinking rubric when implementing Merrill’s First Principles of Instruction.